Molybdenum hexacarbonyl mediated synthesis of indolin-2-one & azaindolin-2-one under catalyst free conditions. Issue 46 (18th November 2015) - Patil, Vikas S.; Pal, Shyam S.; Pathare, Ramdas S.; Reddy, L.K.K.; Pathak, Arunendra
Graphical abstract: Abstract: Syntheses of indolin-2-ones and azaindolin-2-ones have been realized. The strategy involves the formation of tosylhydrazone from tosylhydrazine and 2-amino aryl or pyridyl aldehydes/ketones which then undergo intramolecular aminocarbonylation to afford indolin-2-ones and azaindolin-2-ones. The generality of the method was demonstrated by synthesizing C3 substituted and unsubstituted indolin-2-one and azaindolin-2-one derivatives.